(untitled) (Impetus, 2021)
It is inferred that aggressiveness is inherent in the human being, although in the school context this behavior negatively influences the performance and coexistence in school. In this sense, cooperative games (CG) are activities aimed at fostering prosocial attitudes, seeking the participation of all and particularly making the collective objectives superior to the individual ones. Thus, the aim of this study was to determine the effect of an intervention program based on cooperative games on the level of aggression of third-grade students at the Custodio Garcia Rovira School in Málaga. A 12-week intervention was applied to 60 children (7-12 years) divided into 2 groups (experimental [EXP], control [CTRL]). The program was developed in 3 phases (intrapersonal, interpersonal, interaction in JC) and aggressiveness was evaluated before and after the intervention with the aggressiveness questionnaire (Buss and Perry, 1992), the statistical analysis was means by a 2 factors MANOVA (groups*moment) and it was established p <0.05. The results indicate interaction (group*moment) (Wilks Lambda = 0.514; F1:50 = 2.54; p <0.01; η2 = 0.49) for verbal aggression 2 and 4, also was evidenced a moment main effect (Wilks Lambda = 0.53; F1:50 = 2.45; p = 0.01; η2 = 0.47) for physical aggression 1 and 4, verbal aggression 2 and 4, finally for hostility 1, 2, 3 and 4. In this way, it is concluded that a JC program is effective to reduce aggression in elementary school students.